Output performance, institutions and structural policy reforms for transition economies - Angjellari-Dajci, Fjorentina (Kansas State University, 2005)
This dissertation explores the relationships between three groups of variables in the transition economies of Central and Eastern Europe (CEE) and Commonwealth of Independent States (CIS), from 1989 to 2003. The first group consists of output level and output growth as measured by gross domestic product index (GDPI) and gross domestic product growth (GDPG). The second group consists of two categories of institutional development (INST), and the third group of variables is structural policy reforms (SPR), often known as liberalization policies. This dissertation’s theoretical and empirical framework explicitly account for the endogeneity between output performance variables, the measures of institutional development and SPR. Several empirical specification models of the theoretical simultaneous system of three equations are estimated. In the first group of specification models the dependent endogenous variables are GDPG, SPR and INST, while in the second group the dependant endogenous variables are GDPI, SPR and INST. Moreover, two datasets are used. The first dataset has data from 1989 to 2003, thus covering the whole transition period, while the second dataset is a subset of the first one, containing data for the recovery stage of transition only. The empirical methods used in this dissertation include panel data analysis, principal component analysis, two stages least squares approach and three stage least squares approach in the presence of a SUR modeling procedure. With respect to the output performance equation, the findings of this research indicate that institutional reform (INSTREF), and property rights and contract enforcement institutions (PCINST and ROLINST) are very important determinants of output levels when the whole transition period dataset is used, and very important determinants of both the output levels and output growth rates when the recovery stage dataset is used. While the effect of current SPR is ambiguous, the effect of lagged SPR on output and output growth is positive. Moreover, SPR continue to affect output performance via their indirect effect on institutional development. With respect to the institutional reforms, and property rights and contract enforcement institutions, two sets of determinants were found to be important. On the side of the demand factors, SPR, and especially lagged SPR is found to be an important determinant of both institutional reforms and property rights and contract enforcement institutions. On the side of supply factors, macroeconomic stabilization, a measure of the state’s capacity to implement institutional reform, resulted very important in explaining the variation in institutional reform and property rights and contract enforcement institutions. Political reform, in terms of a shift from the autarkic political regime to a democratic political regime, is found to positively affect institutional development in the recovery stage. With respect to the structural policy reforms’ equations, this dissertation’s main finding is that political reform positively affects SPR in both datasets. Moreover, lagged SPR is found to positively affect SPR, which is an indication of transition governments’ maintained commitment to a package of SPR-s.
Keywords: Economic growth; Transition; Institutions; Political reform; Initial conditions; Economics, General (0501)